Renal transplant ultrasound: The nephrologist's perspective - Leong, Khai Gene (Australas J Ultrasound Med, 2015)
One of the principal roles of a nephrologist is to closely monitor renal transplant allograft function and promptly evaluate any dysfunction. Renal transplant sonography has a major role in this assessment process given its ability to easily define renal transplant anatomy and surrounding structures. Abnormalities can be extrarenal or involve vascular, parenchymal and urological components of the graft and these can acutely or chronically influence graft function and survival. Procedural guidance as is required during allograft biopsy, as well as routine surveillance and screening for post transplant complications such as malignancy are also important applications of ultrasound in the management of renal transplant recipients. This article outlines key ultrasound findings and applications in renal transplantation from the clinician's perspective.